Idioms as an object of linguoculturology - Valieva, Nargizakhon Zamir kizi (The Lingua Spectrum, 2026)
This article examines idioms as a specific object of linguocultural analysis. The study explores major approaches to the classification of phraseological units in the works of leading scholars and identifies the key features that distinguish idioms within the language system. Special attention is paid to the relationship between idiomatic expressions and the cultural code of society, the national worldview, and value orientations of language speakers. The article concludes that idioms function not only as linguistic units but also as culturally significant elements that reflect mentality, historical experience, and figurative thinking of a nation.